“Jack the Stripper” – A cold case review - Berry, M. J. (Advances in Social Sciences Research Journal, 2020)
This cold case is unusual in that the full details have been embargoed for a hundred years yet it has been the source of numerous books about the killer nicknamed ‘Jack the Stripper’. During 1964-1965, six female sex workers were murdered and left naked scattered around London’s Hammersmith area. A number of males were identified as the killer although none were convicted. The writer has incorporated data from eight books and visits to various sites to create a profile; it challenges some of the unsubstantiated claims of the various authors who have written about the murders and who named at least five different killers. It identifies the likely characteristics and questions much that has been written by emotive authors based upon secondary data with the risk that such an approach is used.